The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2174/1566524016666151222143609
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation in treating depression: A tale of two stories.

Abstract: Vagus nerve stimulation (VNS) has been widely used to treat different neurological disorders, especially epilepsy. Accumulating evidence also suggests its potential application in antidepressive therapy, given that VNS has been confirmed by several clinical trials to exert long-term effects on mitigating depression and reducing the risk of relapse in depressed patients. Likewise, VNS has also proven to ameliorate the behavioral deficits in a rat model of depression. While the influences of VNS on monoamine met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…Similar results were found after chronic treatment with fluoxetine [124]. This topic has been reviewed recently [125].…”
Section: Effect On Neurogenesis and Neurotrophinssupporting
confidence: 61%
“…Similar results were found after chronic treatment with fluoxetine [124]. This topic has been reviewed recently [125].…”
Section: Effect On Neurogenesis and Neurotrophinssupporting
confidence: 61%
“…This functional dissociation of taVNS-induced effects is clinically relevant because cost-evidence accumulation is affected by escitalopram, a selective serotonin reuptake inhibitor and common antidepressant drug (Meyniel et al, 2016). Thus, antidepressive effects of VNS (Fang et al, 2016;Grimonprez et al, 2015;Hein et al, 2013;Liu et al, 2016;Tu et al, 2018;Wu et al, 2018;Yuan, Li, Sun, Arias-Carrion, & Machado, 2016) may act via a different neurobehavioral mechanism on the utility of effort than commonly used anti-depressant, pointing to the potential of complementing currently used pharmacological treatment regimes (Argyropoulos & Nutt, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with TRD, VNS has been shown to improve symptoms of depression 79,80. Imaging studies using either single photon emission computed tomography or blood oxygen level-dependent methods revealed that improvement in depression symptoms induced by VNS was associated with decreased activity in the sgACC, VMPFC, and ACC and increased activity of the superior temporal gyrus 81,82…”
Section: Neurobiology Of Mood Disordersmentioning
confidence: 99%